PERAN ORANG TUA DALAM PEMBENTUKAN IDENTITAS GENDER ANAK - Triyani Pujiastuti (JURNAL ILMIAH SYI'AR, 2014)
This paper attempts to look at the role of parents in children’s gender identityformation . The role of parents of early gender development is important in acommunity because it is the smallest and closest sphere in an interpersonalrelationship . This role will be a pattern that forms the character of an individual to the development of gender . The behavior of parents towards their children will be the construction of identity is recorded in the child .